Different Complexation Behavior of P‐Functionalized Ferrocene Derivatives Towards SnCl2, SnCl4 and SnPh2Cl2: Auto‐ionization and Redox‐Type Reactions. Issue 46 (20th October 2015) - Gawron, Matthias; Dietz, Christina; Lutter, Michael; Duthie, Andrew; Jouikov, Viatcheslav; Jurkschat, Klaus
Abstract: The novel phosphonyl‐substituted ferrocene derivatives [Fe(η 5 ‐Cp)(η 5 ‐C5 H3 P(O)(O‐ i Pr)2 2 ‐1, 2)] (Fc 1, 2 ) and [Feη 5 ‐C5 H4 P(O)(O‐ i Pr)2 2 ] (Fc 1, 1′ ) react with SnCl2, SnCl4, and SnPh2 Cl2, giving the corresponding complexes [(Fc 1, 2 )2 SnCl][SnCl3 ] (1 ), [(Fc 1, 1′ )SnCl2 n ] (2 ), [(Fc 1, 1′ )SnCl4 ] (3 ), [(Fc 1, 1′ )SnPh2 Cl2 n ] (4 ), and [(Fc 1, 2 )SnCl4 ] (5 ), respectively. The compounds are characterized by elemental analyses, 1 H, 13 C, 31 P, 119 Sn NMR and IR spectroscopy, 31 P and 119 Sn CP‐MAS NMR spectroscopy, cyclovoltammetry, electrospray ionization mass spectrometry, and single‐crystal as well as powder X‐ray diffraction analyses. The experimental work is accompanied by DFT calculations, which help to shed light on the origin for the different reaction behavior of Fc 1, 1′ and Fc 1, 2 towards tin(II) chloride. Abstract : Small change, big difference : Whereas the phosphonyl‐substituted ferrocene derivative [Fe(η 5 ‐Cp)(η 5 ‐C5 H3 P(O)(O‐ i Pr)2 2 ‐1, 2)] (Fc 1, 2 ) reacts with SnCl2 under auto‐ionization giving the salt [(Fc 1, 2 )2 SnCl][SnCl3 ] (1 ), its closely related analogue [Feη 5 ‐C5 H4 P(O)(O‐ i Pr)2 2 ] (Fc 1, 1′ ) gives, under the same reaction conditions, the coordination polymer [(Fc 1, 1′ )SnCl2 n ] (2 ; see scheme; Cp=Cyclopentadiene).